2008
DOI: 10.1186/1741-7007-6-37
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin enhances hippocampal long-term potentiation and memory

Abstract: BackgroundErythropoietin (EPO) improves cognition of human subjects in the clinical setting by as yet unknown mechanisms. We developed a mouse model of robust cognitive improvement by EPO to obtain the first clues of how EPO influences cognition, and how it may act on hippocampal neurons to modulate plasticity.ResultsWe show here that a 3-week treatment of young mice with EPO enhances long-term potentiation (LTP), a cellular correlate of learning processes in the CA1 region of the hippocampus. This treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
129
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(145 citation statements)
references
References 49 publications
12
129
2
2
Order By: Relevance
“…27 Very recently, we discovered that EPO is able to enhance hippocampal long-term and short-term potentiation and neuronal plasticity, considered prerequisites for learning and memory processes in this brain area. 125 Most intriguingly, we found that EPO prevents the development of slowly progressing global brain atrophy in a mouse model of chronic neurodegeneration. 86 The fact that EPO reduced in vitro haloperidolinduced death of primary hippocampal neurons, further encouraged continuation of our plans to use this compound for treating schizophrenic patients.…”
Section: Schizophreniamentioning
confidence: 78%
“…27 Very recently, we discovered that EPO is able to enhance hippocampal long-term and short-term potentiation and neuronal plasticity, considered prerequisites for learning and memory processes in this brain area. 125 Most intriguingly, we found that EPO prevents the development of slowly progressing global brain atrophy in a mouse model of chronic neurodegeneration. 86 The fact that EPO reduced in vitro haloperidolinduced death of primary hippocampal neurons, further encouraged continuation of our plans to use this compound for treating schizophrenic patients.…”
Section: Schizophreniamentioning
confidence: 78%
“…Many studies have also implicated potential anti-oxidative (Genc et al, 2004;Signore et al, 2006;Xue et al, 2007;Wang et al, 2009) actions of EPO. Few recent reports have documented a prominent role of erythropoietin in process of long term-potentiation (LTP) hence memory formation (Adamcio et al, 2008;El-Kordi et al, 2009). Erythropoietin probably exerts its actions via acting as a ligand for erythropoietin receptors and stimulating erythropoietin receptor mediated signaling cascade, which certainly plays a prominent role in process of LTP and memory (Adamcio et al, 2008;El-Kordi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Few recent reports have documented a prominent role of erythropoietin in process of long term-potentiation (LTP) hence memory formation (Adamcio et al, 2008;El-Kordi et al, 2009). Erythropoietin probably exerts its actions via acting as a ligand for erythropoietin receptors and stimulating erythropoietin receptor mediated signaling cascade, which certainly plays a prominent role in process of LTP and memory (Adamcio et al, 2008;El-Kordi et al, 2009). Therefore it may be put forth that EPO in our investigation attenuated scopolamine -induced memory deficits and associated biochemical changes by virtue of its multiple actions including anti-oxidative, neuroprotective, and anti-cholinesterase actions.…”
Section: Discussionmentioning
confidence: 99%
“…The brains of EPO receptor (EPOR) knockout mice show enhanced apoptosis and the mice are highly sensitive to hypoxia (74), but it is not known if this sensitivity is because EPO has a neuroprotective effect or is a secondary effect of decreased oxygen delivery to the brain. A recent study demonstrates that EPO treatment improves hippocampal-dependent memory by modulating neuronal plasticity and synaptic connectivity, suggesting EPO to be a potential neuropsychiatric drug (75). Image analysis in clinical research has shown that EPO rapidly improves mood and modulates cognitive neural processing, as do serotonergic antidepressant drugs (59).…”
Section: Neurotrophic Factors Affecting Adult Hippocampal Neurogenesimentioning
confidence: 99%